A review on Halal and Kosher regulations, certifications, and industrial practices - Mohd Shuhaimi, Amarul Arief; Ab Karim, Muhammad Shahrim; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Arsyad, Mohd Mursyid (Human Resource Management Academic Research Society, 2022)
Halal and Kosher generally may have shared certain attributes as both were originated within Abrahamic religions. The globalization and internalization of food industry has encouraged both dietary laws to pursue standards regulatory and procedures not only to preserve their laws and beliefs but also to provide better services to their respective markets around the globe. The purpose of this paper is to compare halal and kosher practices and in depth understanding of both laws and provide an overview of the industrial practices, regulations, and certifications of both laws in spearheading challenges in the current era. Reviews of past studies were made to get a grasp understanding in regard to these two dietary laws.